2023
DOI: 10.1039/d2sc05660g
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of interleukin-2 via a tunable backbone modification strategy

Abstract: Chemical synthesis of hydrophobic proteins presents a formidable task, as hydrophobic peptides are often difficult for peptide synthesis, purification and performing peptide ligation. Thus, peptide solubilizing strategies are needed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Increasing the solubility and reactivity of these “difficult peptides” is long‐lasting question in peptide chemistry [66] . Some recently developed technologies like ligation embedding aggregation disruptor (LEAD), [67] tunable backbone modification (TBM) [68] and reducible solubilizing tags (RSTs) [69] are worth to be tested. We hope this short review could be helpful for the scientists who plan to start their adventure in this field and inspire the development of new methods to tackle the challenges in both synthetic protein chemistry and chemical biology.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the solubility and reactivity of these “difficult peptides” is long‐lasting question in peptide chemistry [66] . Some recently developed technologies like ligation embedding aggregation disruptor (LEAD), [67] tunable backbone modification (TBM) [68] and reducible solubilizing tags (RSTs) [69] are worth to be tested. We hope this short review could be helpful for the scientists who plan to start their adventure in this field and inspire the development of new methods to tackle the challenges in both synthetic protein chemistry and chemical biology.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of NBDs stemmed from our long‐term pursuit of controlling peptide chain behaviors to avoid aggregation and truncation. Previously, we found that the N,O / S ‐benzylidene acetal intermediate after STL and CPL could effectively prevent peptide aggregation due to self‐assembling [31] and could be used to introduce solubilizing tags [38] as the ligation embedding aggregation disruptor, and tunable backbone modification, respectively. Thus, we envisioned that the installation of a pre‐formed NBD building block might kink the peptide conformation and facilitate “difficult peptide” synthesis on resin for SPPS.…”
Section: Figurementioning
confidence: 99%
“…Despite these achievements, chemical ligation of unprotected peptides bearing highly hydrophobic regions remains a challenging mission. To overcome this obstacle, various innovative strategies, such as ligation embedding aggregation disruptor, [31] solubilizing tags installation, [32][33][34][35][36] removable backbone modification [37] and tunable backbone modification, [38] have been developed to alter the hydrophobic nature by adding hydrophilic tags and enable solubilizing peptides in the ligation solvent.…”
mentioning
confidence: 99%
“…[19,22] After treating with trifluoroacetic acid (TFA) cocktail, both NBA and NBT can be acidolyzed to produce the native peptide bond at the ligation site, albeit for NBTs much harsher conditions and longer time are required. [14] Till now both STL and CPL have been successfully applied for the chemical syntheses of various valuable peptides/proteins including immune checkpoint proteins, [23] cytokines, [24,25] nucleosome-associated proteins with PTMs, [26][27][28][29][30] antimicrobial cyclic peptides, [31][32][33][34] etc. Importantly, the generated NBA/NBT intermediate during STL/CPL becomes advantageous in challenging protein synthesis since the highly twisted structure of NBA and NBT can serve as an aggregation disruptor, which allows us to complete the first chemical synthesis of the immune checkpoint protein programmed cell death protein 1 (PD-1) extracellular domain.…”
Section: Introductionmentioning
confidence: 99%